ANALISIS WILLINGNESS TO PAY KERETA API KOMUTER SIDOARJO - INDRO - Hafizhudin Alfin Putra Yuwanto; Nugroho Utomo; Fithri Estikhamah (Racic : Rab Construction Research, 2024)
The high level of economic activity and population density has resulted in Surabaya City, Gresik Regency, and Sidoarjo Regency experiencing a high level of community mobility, necessitating good public transportation services. Therefore, on February 10, 2021, PT. Kereta Api Indonesia (Persero) Regional Operation 8 Surabaya initiated passenger train services in Gresik Regency by operating the Commuter Train with the route from Indro Station (Gresik) to Sidoarjo Station. This study aims to determine a fare that is suitable for the Commuter Train service from Sidoarjo to Indro using the willingness to pay (WTP) method. Based on the research findings, the willingness to pay value for the Sidoarjo-Indro Commuter Train journey with the existing fare of Rp 5,000 is Rp 7,700. Therefore, the current fare is deemed appropriate, and it can still be increased with improvements in facilities and services.